Manajemen Implementasi Perpaduan Kurikulum Cambridge dan Kurikulum Nasional di SMP Islam Alabidin Surakarta - Ahmad Bayu Abdulloh; Imam Makruf (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Increasing public awareness of the importance of education has enriched efforts to find educational models that are more appropriate, effective and futuristic. This study aims to describe and analyze how management integrates the Cambridge curriculum and the national curriculum. What are the advantages and disadvantages of integrating the Cambridge curriculum and the national curriculum. This research uses a qualitative approach, conducted at the Alabidin Islamic Middle School in 2021. The research subject is the deputy principal of the curriculum section. While the research informants were school principals, International Class Program (ICP) teachers and some International Class Program (ICP) students. Data collection techniques through observation, interviews, and documentation. Data validation techniques use data triangulation and method triangulation. Data analysis techniques use interactive analytical models.. The results of this study indicate. Integration of curriculum implementation management with (a) Planning, preparation of Curriculum documents, RPP, Syllabus, framework, SOW (Scheme Of Work), Lesson Plan,. (b) organization includes the selection of human resources who are competent in their fields. (c) the implementation of the integrated curriculum is taken in parallel with the adaptive adoption method. aticve learning. (d) Controlling student learning with evaluation (Mid-Semester Assessment) and (Final Semester Assessment) and (CPT) check progression test and checkpoint for grade 9. The advantage is that students gain global knowledge, the complexity of critical and creative thinking, skill language increases. The weakness is that students still have difficulty understanding what the teacher conveys in English material. environment that is less conducive to English communication in the school.